(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The objective of this study is to know the contributions of Micro finance towards employment development through generating employment opportunities to the alit class of urban and rural community. For this purpose quantitative research techniques were used to collect the data. The data was collected through secondary sources from economic survey from 2011-12 and labor force survey 2010-2011 and from annual plans of Pakistan from 2001-02 toÂ Â 2012-13. Mainly 8 to 10 micro finance banks and micro finance institutes and some NGOs are taken into study. Â The results express the positive contributions of micro finance to the employment that leads to poverty reduction and improved living standard. In contrast micro finance through supporting the employment generates sustainable solutions of other economic problems like poverty, good education, better health etc.Â